Salt Marshes as Groundwater Buffers for Development: A Survey of South Carolina Salt Marsh Basins - Wilson, Alicia M.; Shanahan, Meghan; Smith, Erik M. (Frontiers in Water, 2021)
Salt marshes serve as zones of intense groundwater mixing and reaction between freshwater uplands and estuaries. This raises the question of whether the impacts of upland development on nutrient and carbon species can be transmitted through salt marshes via groundwater, or whether salt marshes can buffer estuarine waters from coastal development. We sampled groundwater from fifteen tidal creek basins in South Carolina to test for compositional differences associated with development and marsh width. Groundwater samples from near creekbanks and below freshwater uplands were analyzed for salinity, total dissolved nitrogen and phosphorus, and dissolved organic carbon. Analyses revealed significantly higher TDN and TDP concentrations in creekbank samples from developed watersheds, independent of the season. Analyses of upland samples revealed significantly lower DOC concentrations in developed uplands, again independent of season. These results support the hypothesis that development can affect groundwater compositions in coastal groundwater and therefore may affect coastal nutrient and carbon fluxes. However, results also revealed significant linear correlations between marsh width, salinity, and nutrient concentrations in some marshes. These results suggest that salt marshes can act as buffers for development, and specifically suggests that the buffering capacity of salt marshes increases with width. Narrow or trenched salt marshes are far less likely to be effective buffers.